2015
DOI: 10.1103/physrevb.91.195441
|View full text |Cite
|
Sign up to set email alerts
|

Barrier-free subsurface incorporation of3dmetal atoms into Bi(111) films

Abstract: By combining scanning tunneling microscopy with density functional theory it is shown that the Bi(111) surface provides a well-defined incorporation site in the first bilayer that traps highly coordinating atoms such as transition metals (TMs) or noble metals. All deposited atoms assume exactly the same specific sevenfold coordinated subsurface interstitial site while the surface topography remains nearly unchanged. Notably, 3d TMs show a barrier-free incorporation. The observed surface modification by barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In fact, that structural disorder is a result of the alloy formation, is in line with the growth mode found for Bi on Si(111): A 40 BL Bi-film, shown in figure 1(e), which has nominally a larger misfit to Si(111), reveals almost no rotational disorder [22,25]. For reasons of comparison the Bi-film was grown at the same conditions, i.e.…”
Section: Resultssupporting
confidence: 80%
“…In fact, that structural disorder is a result of the alloy formation, is in line with the growth mode found for Bi on Si(111): A 40 BL Bi-film, shown in figure 1(e), which has nominally a larger misfit to Si(111), reveals almost no rotational disorder [22,25]. For reasons of comparison the Bi-film was grown at the same conditions, i.e.…”
Section: Resultssupporting
confidence: 80%
“…Note that TM atoms can be incorporated into the surface layer of Bi(111) films without vacancies. 40 Due to the structural difference between the Bi(111) film and single Bi bilayer, the stabilities of the TM in these two systems are different. Table 1 The calculated geometrical parameters of Bi(111) with transition metal trapped at the divacancy site Electronic and magnetic properties of TM/DV/Bi(111).…”
Section: B Bi(111) Dvs Decorated With Tm Atomsmentioning
confidence: 99%
“…20,[34][35][36] Meanwhile, several theoretical and experimental works suggest that the transition metal decoration can induce spin polarization in graphene and also in Bi(111) films due to a strong d-p orbital interaction between the TM atom and graphene, respectively. [37][38][39][40] It can be anticipated that graphene-like Bi(111) may also exhibit spin polarized features, when decorated with TMs. It is noteworthy that unlike graphene, Bi(111) exhibits a trigonal pyramidal geometry with a finite band gap.…”
Section: Introductionmentioning
confidence: 99%
“…By combining scanning tunneling microscopy with density functional theory, Klein et al has shown that the Bi (111) surface provides a well-defined incorporation site in the first bilayer that traps highly coordinating atoms such as transition metals or noble metals. [15] However, the transport study of the impurities effect on surface states are mainly in poly crystalline Bi films, [16][17][18] in which the surface has no well defined orientation. It is still not clear how the impurities would affect the surface conductivity and the phase coherence length in the Bi (111) surface states.…”
Section: Introductionmentioning
confidence: 99%